Bodily self-perception during voluntary actions: The causal contribution of premotor cortex and cerebellum. (September 2021) - Marotta, Angela; Re, Anna; Zampini, Massimiliano; Fiorio, Mirta
Abstract: Voluntary actions are accompanied by the experience of controlling one's own movements (sense of agency) and the feeling that the moving body part belongs to one's self (sense of body ownership). So far, agency and body ownership have been investigated separately, leaving the neural underpinnings of the relation between the two largely unexplored. The aim of this study was to explore the causal role of two multisensory brain regions, that is the premotor cortex (PMc) and the cerebellum, in agency and body ownership concurrently on the same behavioral task, i.e., the moving Rubber Hand Illusion (mRHI). Participants watched a rubber hand while moving their hidden hand. The type of movement (active or passive) and posture of the rubber hand (congruent or incongruent) differed in three conditions (active congruent, passive congruent, active incongruent), so that agency and ownership could be elicited either separately or concurrently. Agency and ownership were measured by subjective report and proprioceptive drift. Sham and anodal transcranial direct current stimulation (tDCS) were delivered to the PMc (Experiment 1) or the cerebellum (Experiment 2) prior to the mRHI task. Independent of the site or type of tDCS, subjective reports revealed that both agency and ownership were evoked in the active congruent condition, ownership but not agency in the passive congruent condition, and agency but not ownership in the active incongruent condition. The proprioceptive drift was evoked in the active congruent and the passive congruent condition. Anodal tDCS over the PMc reduced the feeling of agency in the active congruent condition, while it enhanced proprioceptive drift when applied over the cerebellum. These findings suggest a specific causal contribution of the PMc and the cerebellum to bodily self-perception during voluntary movement, with the PMc mainly involved in awareness of action and the cerebellum in proprioceptive adaptation of body position in space.